Molecular characterization of ageratum enation virus and beta satellite associated with leaf curl disease of fenugreek in India - P Swarnalatha; V Venkataravanappa; C N Lakshminarayana Reddy; M Sunil Kumar; M Krishna Reddy (Universitas Gadjah Mada, 2019)
Cisplatn is one of the chemotherapy for the treatment of triple‐negatve breast cancer (TNBC), but its eﬀectveness is limited because of the phenomenon of chemoresistance. miR‐638 was shown to regulate chemoresistance; however, it has never been validated in the cisplatn‐resistant tumor from patents. This present study aimed to identfy the key gene regulatory networks of miR‐638 and evaluate the potental role of the miR‐638 and its targets as potental prognosis biomarkers for cisplatn‐resistance triple‐negatve breast cancer patents. The miR‐638 target was obtained from the miRecords database while the mRNA of chemoresistance biomarker candidate was obtained from the GSE18864 of GEO database, which is mRNA of cisplatn‐resistance TNBC patents. CCND1 and FZD7 are potental candidates for cisplatn chemoresistance biomarkers in patents with TNBC. Moreover, a Kaplan‐Meier survival plot showed that breast cancer patents with low mRNA levels of FZD7 had signifcantly worse overall survival than those in higher mRNA expression group. Taken together, miR‐638 plays a role in cisplatn resistance mechanism through a mechanism involving its target gene CCND1 and FZD7. Overall, miR‐638, CCND1, and FZD7 are candidates for cisplatn biomarker resistance in TNBC.